Seven years later: Casinos in the aftermath of the 2005 Gambling Act - Christopher Snowdon (Institute of Economic Affairs (IEA), 2012)
A new IEA publication explores the case for deregulating the gambling marketExecutive summary:The 2005 Gambling Act was intended to modernise gambling in the United Kingdom by replacing the anachronistic 1968 Gaming Act with legislation better suited to the twenty-first century. The 1968 Act had placed tight restrictions on the number of casinos that could open and these were limited to specified towns and regions. Gambling machines and jackpots were also strictly limited.The Blair government originally endorsed extensive liberalisation of the casino industry which would have effectively allowed the market to dictate how many casinos were in operation, subject to permission from local authorities and the Gambling Commission.It would have permitted a larger number of high stake jackpot and virtual gambling machines and would have allowed the creation of large entertainment complexes ('resort casinos') of the type seen overseas.In the months leading up to the 2005 General Election, sections of the media, faith groups and parts of the incumbent gambling industry led a campaign against the Gambling Bill which focused on so-called 'Las Vegas style super-casinos' and their supposed threat to British society. Faced with this backlash, the government hastily rewrote parts of the draft legislation pertaining to casino regulation. Limits were placed on the number of new casinos that could be opened and the number of resort casinos was reduced, ultimately to zero.By the time the legislation received Royal Assent in April 2005 it had not only been stripped of its boldest attempts at liberalisation but had also lost many of the uncontroversial reforms needed to allow casinos to compete in a rapidly changing marketplace.Specifically, it maintained the prohibition on opening casinos across large tracts of the country and failed to allow casino licences to be transferred from one region to another.As a consequence, many large towns are still unable to open casinos, regardless of public demand, and dozens of licences remain dormant. Seven years later, only one of the 16 casino licences created by the Act is in use.The 2005 Act placed new restrictions on the number of gambling machines that could be hosted in casinos and strictly limited the types of games and prizes available. Although casino regulation (and taxation) has always placed casinos at the top of the regulatory pyramid, current legislation is no longer commensurate with their status as 'the safest place to gamble'. Although casinos cannot offer online gaming or betting on horse-racing, for example, most casino games can now be played on the high street, on a mobile phone and on the internet for similar, or even higher, stakes.No one wants to see 'blackjack on every street corner', as the Daily Mail once put it, but there is no obvious reason why a reasonably sized town or city should not be able to host at least one small casino if the community is in accord. A more coherent regulatory structure would allow casinos to offer games, stakes and prizes which are consistent with their position at the top of the pyramid. The law should allow British casino operators to tailor their offering to consumer preference as their international competitors do. No new legislation would be required to fix the regulatory inconsistencies that the 2005 Act created and the economic benefits in terms of job creation and tax revenues would not be trivial.
Keywords: 330; Gambling; Regulation; Great Britain; Glücksspiel; Regulierung; Großbritannien